PRODUCTION AND ECONOMIC INDICATORS OF CORN SILAGE PRODUCTION IN BOSNIA AND HERZEGOVINA - Falan, Vedad; Mujčinović, Alen; Bećirović, Emir (Journal on Processing and Energy in Agriculture, 2021)
The highest quality silage is produced from corn (corn silage), which is also the most common livestock feed. The lack of corn silage in livestock production can be compensated only by concentrated feed, which is usually more expensive, but this is a well-applied practice in B&H. Therefore, the main aim of this paper was to determine the economic viability of corn silage production in B&H for the period 2014-2019. Primary data for this research were collected based on a semi-structured interview with representatives of the farm "Farma Spreča" Kalesija with a total harvested area of 500 ha. Results indicate that with total harvested area increases 61.29%, yield increases only 6.26%, while efficiency decreased by 6.38% implying problems related to productivity. Based on that, corn silage production in B&H shows positive financial performances, but low yield even with a strong increase in harvested areas indicates the need for further technological and technical improvement.
Keywords: corn silage, livestock production, economic analysis, cost management